The fourth industrial revolution and the skills mismatch within the Business Analysis Profession - Mukozho, Denise (Department of Information Systems, 2024)
This study describes the skills mismatch within the Business Analysis profession during the Fourth Industrial Revolution. The Business Analysis profession is a new information systems field that emerged in the early 1990s and requires extensive research. The Fourth Industrial Revolution is projected to result in a skills mismatch. This study uses the Business Analysis Competency Model, Social Cognitive Career Theory and a mixed-methods research design to develop a framework for describing the skills mismatch within the Business Analysis profession. Reviewed literature highlighted four key categories of skills (technical, business, personal/attitudinal and interpersonal skills). The study found that there are various mismatches between current and future roles. Personal, interpersonal, and business skills are relatively constant between the two roles whereas technical skills show significant mismatches between the current and future roles. This study proposes a skills mismatch framework for addressing a possible Fourth Industrial Revolution-induced skills mismatch.